Effects of different signaling pathways on odontogenic differentiation of dental pulp stem cells: a review - Zhou, Lisha; Zhao, Shuya; Xing, Xianghui (Frontiers in Physiology, 2023)
Dental pulp stem cells (DPSCs) are a type of mesenchymal stem cells that can differentiate into odontoblast-like cells and protect the pulp. The differentiation of DPSCs can be influenced by biomaterials or growth factors that activate different signaling pathways in vitro or in vivo. In this review, we summarized six major pathways involved in the odontogenic differentiation of DPSCs, including Wnt signaling pathways, Smad signaling pathways, MAPK signaling pathways, NF-kB signaling pathways, PI3K/AKT/mTOR signaling pathways, and Notch signaling pathways. Various factors can influence the odontogenic differentiation of DPSCs through one or more signaling pathways. By understanding the interactions between these signaling pathways, we can expand our knowledge of the mechanisms underlying the regeneration of the pulp-dentin complex.